Achieving an ultra-narrow multiband light absorption meta-surface via coupling with an optical cavity. (19th May 2015) - Liu, Zhengqi; Liu, Guiqiang; Liu, Xiaoshan; Huang, Shan; Wang, Yan; Pan, Pingping; Liu, Mulin
Abstract: Resonant plasmonic and metamaterial absorbers are of particular interest for applications in a wide variety of nanotechnologies including thermophotovoltaics, photothermal therapy, hot-electron collection and biosensing. However, it is rather challenging to realize ultra-narrow absorbers using plasmonic materials due to large optical losses in metals that inevitably decrease the quality of optical resonators. Here, we theoretically report methods to achieve an ultra-narrow light absorption meta-surface by using photonic modes of the optical cavities, which strongly couple with the plasmon resonances of the metallic nanostructures. Multispectral light absorption with absorption amplitude exceeding 99% and a bandwidth approaching 10 nm is achieved at the optical frequencies. Moreover, by introducing a thick dielectric coupling cavity, the number of absorption bands can be strongly increased and the bandwidth can even be narrowed to less than 5 nm due to the resonant spectrum splitting enabled by strong coupling between the plasmon resonances and the optical cavity modes. Designing such optical cavity-coupled meta-surface structures is a promising route for achieving ultra-narrow multiband absorbers, which can be used in absorption filters, narrow-band multispectral thermal emitters and thermophotovoltaics.